Pelatihan Pengoperasian Mesin CNC Milling di SMTK Sabu Raijua, Nusa Tenggara Timur - Aryantono Mortowidjojo; Sesmaro Max Yuda; Medyawanti Pane; Stepanus; Ivan Julius Rajagukguk; Zefanya Sipahelut; Melky Hendrik kelo; Maria Helena Putri Nira; Jonathan Oliver Kislew Tanuwidjaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The development of technology is increasingly rapid, especially in the world of machinery or industry, so improving the competence of student graduates is very important to prepare the workforce needed in the industrial environment. SMTK Sabu Raijua East Nusa Tenggara is currently unable to have a craft technique based on science and technology that supports the industrial era 4.0. as an initial competency in the production process for small and medium industries in the field of manufacturing technology and engineering. Therefore, the Universitas Kristen Indonesia through the PkM Team, conducted CNC milling machine programming training for teachers and students. This training aims to improve the abilities or competencies of students in preparation for entering the industrial world which is packaged in extracurricular lessons. The method of implementing this PkM activity uses the training and evaluation method. This training activity includes selecting milling eyes, a simple product design process on Vetric software, creating G-Code files on Vetric software, calibration between system coordinates and machine coordinates, and operating CNC machines. The training was attended by 36 participants consisting of students and teachers of SMK HKBP Pematang Siantar on January 27-29, 2025. After training and observation, it was concluded that participants were able to produce simple products such as key chains based on CNC machines according to the standards determined by the team.